Comparative analysis of cultural elements in the fairy tales of “Timun Mas” and “Momotaro” - Ramadhani, Anis Kusuma; Rachmawati, Enna; Siagian, Irwan (Universitas Dian Nuswantoro, 2021)
This study aims to analyze and describe the comparison of cultural elements found in the Indonesian fairy tale